Blockchain-based approaches to the issue of de-risking - Williams, Roger Crane (2017)
Posits that blockchain technology appears to have the potential to address the problem of de-risking on two front: a) an appropriately designed blockchain-based settlement network could ease the process of moving funds internationally, by offering tools to improve surveillance of transactions; b) a blockchain-based network would offer Caribbean banks the opportunity to bypass correspondent banks altogether and so reduce transaction costs and increase efficiency.